Differential Effects of the Mitochondria-Active Tetrapeptide SS-31 (D-Arg-dimethylTyr-Lys-Phe-NH2) and Its Peptidase-Targeted Prodrugs in Experimental Acute Kidney Injury - Wyss, Jean-Christophe; Kumar, Rajesh; Mikulic, Josip; Schneider, Manfred; Mary, Jean-Luc; Aebi, Johannes D.; Juillerat-Jeanneret, Lucienne; Golshayan, Dela (Frontiers in Pharmacology, 2019)
The mitochondria-active tetrapeptide SS-31 can control oxidative tissue damage in kidney diseases. To investigate other potential beneficial nephroprotective effects of SS-31, in vivo murine models of acute tubular injury and glomerular damage were developed. Reduction of acute kidney injury was demonstrated in mice treated with SS-31. The expression of mRNAs involved in acute inflammatory and oxidative stress responses in the diseased kidneys confirmed that SS-31 could regulate these pathways in our in vivo models. Furthermore, ex vivo histoenzymography of mouse kidneys showed that aminopeptidase A (APA), the enzyme involved in the processing of angiotensin (Ang) II to Ang III, was induced in the diseased kidneys, and its activity was inhibited by SS-31. As the renin-angiotensin system (RAS) is a main regulator of kidney functions, the regulation of the Ang receptors and APA by SS-31 was further investigated using real-time qPCRs performed on mRNAs extracted from diseased kidneys. Following acute tubular and/or glomerular damage, the expression of the AT1R mRNA was upregulated, which could be selectively down-regulated upon SS-31 administration to the animals. At the same time, SS-31 was able to increase the expression of the AT2R, which may contribute to limit renal damage. Consequently, SS-31-based prodrugs were developed as substrates and/or inhibitors for APA and were screened using cells expressing high levels of APA, showing selective regulation by α-Glu-SS-31. Thus, a link between SS-31 and the RAS opens new therapeutic implications for SS-31 in kidney diseases.